2005
DOI: 10.1186/1471-2369-6-3
|View full text |Cite
|
Sign up to set email alerts
|

Surgical revascularization versus amputation for peripheral vascular disease in dialysis patients: a cohort study

Abstract: Background: Surgical treatment of peripheral vascular disease (PVD) in dialysis patients is controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…This may reflect the very high perioperative mortality rate associated with LEA. The 30-day mortality after major amputation has been reported to be as high as 16% in patients on dialysis (21). Our study confirms that diabetes-related LEAs are associated with high 5 and 10-year mortality rates (5, 2224).…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect the very high perioperative mortality rate associated with LEA. The 30-day mortality after major amputation has been reported to be as high as 16% in patients on dialysis (21). Our study confirms that diabetes-related LEAs are associated with high 5 and 10-year mortality rates (5, 2224).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that, regardless of the patient's history of PVD, amputations were far more common than revascularization procedures during the course of dialysis. This was not surprising given that amputations are often the first procedure in patients with ESRD and PVD and that revascularizations in these patients are associated with poor outcomes, including subsequent amputation and mortality (11,24 -26); however, amputations are also associated with increased mortality in dialysis patients (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…29 A close temporal association between the first recorded foot ulcer and the onset of renal replacement therapy has been reported. [33][34][35] The risk of death is high both early after amputation (within 30 days) and within the first year. 31 However, only patients on dialysis are at an increased risk of amputation after a revascularization procedure.…”
Section: Discussionmentioning
confidence: 99%
“…30 Revascularization procedures, which in addition to saving the legs are associated with lower mortality than amputation at all levels of renal function, are less frequent in patients with stages 3 to 5 of chronic kidney disease or on dialysis than those with estimated glomerular filtration rate 460 mL/min per 1.72 m 2 . 34 Male sex, diabetes, previous diagnosis of peripheral vascular disease, high mean predialysis systolic pressure, and high serum phosphorus concentration are predictors of amputation in HD patients. 32 Mortality after amputation is high in dialysis patients.…”
Section: Discussionmentioning
confidence: 99%